Developing Writing Module “Retisa de Rikayat” South Sumatera - Dessy Wardiah; Dian Nuzulia Armariena (STAI Hubbulwathan Duri, 2021)
This research and development is motivated by the desire and hope of materializing learning materials that have relevance to the learning and psychological needs of Indonesian Language Education students, especially giving the effect of a writing culture embedded in students. The long-term goal is the formation of independent, creative, and productive student literacy characters in an effort to empower themselves to explore the ability to write literary works, especially folklore. The modules are developed based on the Rowntree development model. The procedure is divided into three main stages, namely needs analysis, developing draft modules, and evaluating expert lecturers. The subjects of this study were students of Indonesian Language Education FKIP, PGRI Palembang University who took the Literature Writing course. To measure the level of validation of the writing module, Retisa de Rikayat in supporting the mastery of the ability to write literary works was evaluated by expert lecturers in the field of Indonesian language. The writing module of Retisa de Rikayat is quite effective as an alternative complementary teaching material for writing literary works, especially learning to write folk tales. This is in accordance with the results of the assessment, this module has an average score of 76.8 from expert lecturers which is in the good category and is arranged according to the analysis of student needs.